Essentials of Chinese Medicine - Liu, Zhanwen; SpringerLink (Online service) (London : Springer London, 2010)
The modern medical model is gradually shifting from one of biomedicine to one that integrates practices from the physiological, psychological, sociological and medical fields. This growing recognition that people, the environment, ecological conditions and society are all aspects of a united whole has given rise to an emergence of alternative medicine and therapies, many of which are borrowed from traditional Chinese medicine. Essentials of Chinese Medicine systematically introduces the basic theories, diagnostic methods, therapeutic practices, and the principles of health preservation and rehabilitation of the Chinese medical tradition. The basic theories and methods of acupuncture and moxibustion are explained, and a range of Chinese herbs are illustrated. The textbooks also introduces 84 Chinese herbal formulas and 6 associated formulas commonly used in clinical practice. Furthermore, it elucidates treatments of commonly and frequently encountered diseases in internal medicine, surgery, gynecology, pediatrics, ophthalmology and otorhinolaryngology. With a strong emphasis on the fundamental principles of Chinese Medicine, this three-volume set provides concise and systematic content that is suitable for both teaching and self-study.
Basic Theories of Chinese Medicine -- Formation of the Chinese Medicine Theoretical System and Its Philosophical Basis -- Chinese Medicine Methodology -- Structure and Functions of the Human Body -- Basic Substances of Vital Activities -- Etiology in Chinese Medicine -- Pathology in Chinese Medicine -- Diagnostic Methods and the Therapeutic Principles of Chinese Medicine -- Approach to Chinese Medical Diagnosis -- Diagnostic Methods -- Differential Diagnosis -- Therapeutics -- Health Preservation -- Meridians, Acupuncture and Moxibustion -- Meridians: General Introduction -- Overview of Acupoints -- Descriptions of Specific Acupoints -- Techniques of Acupuncture and Moxibustion -- Principles of Acupuncture Therapeutics -- Chinese Materia Medica -- Basic Theory of Chinese Materia Medica -- Commonly Used Herbs -- Chinese Medicinal Formulas -- Basic Principles of CM Herbal Formulation -- Commonly Used Herbal Formulas -- Common Internal Medicine Disorders -- Wind-Injury (Common Cold) -- Cough -- Wheezing -- Asthma -- Palpitation of Heart -- Angina Pectoris -- Insomnia -- Depression -- Stomachache -- Vomiting -- Diarrhea -- Abdominal Pain -- Dysentery -- Constipation -- Stroke -- Vertigo and Dizziness -- Subcostal Pain -- Jaundice -- Edema -- Dysuria -- Impotence -- Lumbago -- Headache -- Rheumatism -- Flaccidity -- Diaphoresis -- Diabetes (Xiao-Ke) -- Abdominal Masses and Obstruction -- Common Gynecological Disorders -- Abnormal Menstruation -- Dysmenorrhea -- Amenorrhea -- Anovulatory Functional Uterine Bleeding -- Vaginal Discharge -- Chronic Pelvic Inflammation -- Infertility -- Threatened and Spontaneous Abortion -- Menopause -- Common Pediatric Illnesses -- Anorexia -- Infantile Cough -- Enuresis -- Diarrhea -- Acute Convulsion -- Common Surgical and Dermatological Conditions -- Eczema -- Urticaria -- Acne Vulgaris -- Contact Dermatitis -- Neurodermatitis -- Cutaneous Pruritus -- Alopecia -- Folliculitis -- Facial Boils -- Carbuncle -- Erysipelas -- Shingles -- Urinary Stones -- Hemorrhoid -- Acute Lumbar Sprain -- Tennis Elbow -- Common Disorders of the Sensory Organs -- Acute Conjunctivitis -- Sudden Deafness -- Acute Naso-Sinusitis -- Chronic Naso-Sinusitis -- Allergic Rhinitis -- Recurrent Ulcerative Stomatitis -- Acute Tonsillitis -- Some Emergency Conditions -- Syncope -- Shock -- Seizure -- High Fever.
Keywords: Medicine; Alternative medicine; Dermatology; Internal medicine; Medicine & Public Health; Complementary & Alternative Medicine; Medicine/Public Health, general; Internal Medicine; Dermatology